Mapping Replication Timing in Single Mammalian Cells. Issue 1 (5th January 2022) - Bartlett, Daniel A.; Dileep, Vishnu; Baslan, Timour; Gilbert, David M.
Abstract: Replication timing (RT) is the temporal order in which genomic DNA is replicated during S phase. Early and late replication correlate with transcriptionally active and inactive chromatin compartments, but mechanistic links between large‐scale chromosome structure, transcription, and replication are still enigmatic. A proper RT program is necessary to maintain the global epigenome that defines cell identity, suggesting that RT is critical for epigenome integrity by facilitating the assembly of different types of chromatin at different times during S phase. RT is regulated during development and has been found to be altered in disease. Thus, RT can identify stable epigenetic differences distinguishing cell types, and can be used to help stratify patient outcomes and identify markers of disease. Most methods to profile RT require thousands of S‐phase cells. In cases where cells are rare (e.g., early‐stage embryos or rare primary cell types) or consist of a heterogeneous mixture of cell states (e.g., differentiation intermediates), or when the interest is in determining the degree of stable epigenetic heterogeneity within a population of cells, single‐cell measurements of RT are necessary. We have previously developed single cell Repli‐seq, a method to measure replication timing in single cells using DNA copy number quantification. To date, however, single‐cell Repli‐seq suffers from relatively low throughput and high costs. Here, we describe an improved single‐cell Repli‐seq protocol that uses degenerate oligonucleotide–primed PCR (DOP‐PCR) for uniform whole‐genome amplification and uniquely barcoded primers that permit early pooling of single‐cell samples into a single library preparation. We also provide a bioinformatics platform for analysis of the data. The improved throughput and decreased costs of this method relative to previously published single‐cell Repli‐seq protocols should make it considerably more accessible to a broad range of investigators. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Whole Genome Amplification (WGA) of single cells and sequence library construction. Basic Protocol 2 : Deriving and displaying single‐cell replication timing data from whole genome sequencing.